Simulasi Pengaruh Bahaya Gadget Terhadap Anak SDN 48 Kota Bengkulu - safitri, melinia; Marga Handayani, Kurnia; Arisandi, Vini; Darnita, Yulia; Muntahanah; Toyib, Rozali (Universitas Muhammadiyah Bengkulu, 2024)
This research aims to simulate and analyze the impact of gadget dangers on children at SDN 48 Kota Bengkulu, utilizing a method that involves the socialization of gadget danger awareness through videos and PowerPoint presentations. With the phenomenon of children being increasingly influenced by excessive gadget use, this study focuses on potential health and behavioral effects such as fatigue, sleep disturbances, blurred vision, dizziness, and the use of inappropriate language. Additionally, this article discusses proposed solutions to mitigate these risks, specifically through the introduction of gadget dangers to the health and development of children. Keywords: Gadget dangers, children, health, child development, socialization